A novel multimodal pharmacologic approach using guanfacine, N-acetylcysteine, and donepezil in severe TBI: a case series - Fesharaki-Zadeh, Arman; Belliveau, Timothy; Pietrzak, Robert H.; Arnsten, Amy (Frontiers in Rehabilitation Sciences, 2025)
Traumatic brain injury (TBI) remains a leading cause of long-term morbidity and disability worldwide. Individuals with moderate to severe TBI often experience persistent neurocognitive deficits, including short-term memory loss, executive dysfunction, and slowed cognitive processing for which there are currently no FDA-approved treatments. This case series investigates the synergistic use of guanfacine, N-acetylcysteine (NAC), and donepezil (GND) administered alongside ongoing cognitive rehabilitation, with treatment effects evaluated through pre- and post-intervention Montreal Cognitive Assessment (MoCA) scores. The guanfacine/NAC combination has previously been reported to improve working memory and executive function in individuals with mild TBI, suggesting its potential applicability to more severe TBI cases. Guanfacine, an alpha-2A agonist approved for ADHD, enhances prefrontal cortical function; Donepezil, a cholinesterase inhibitor, is widely used to treat cognitive symptoms in mild cognitive impairment and early dementia; and NAC, a potent antioxidant and glutamate modulator, has demonstrated neuroprotective effects across a range of clinical contexts, including TBI. Each of these agents has a well-established safety profile. The encouraging outcomes observed in this case series underscore the potential of the GND regimen as a multimodal pharmacologic approach to target the complex neurochemical disruptions following TBI. These preliminary findings warrant further investigation in larger, placebo-controlled trials in order to more rigorously assess the safety, efficacy, and translational potential of this intervention for mitigating chronic cognitive sequelae in individuals with moderate to severe TBI.